2012
DOI: 10.1111/j.1360-0443.2012.03837.x
|View full text |Cite
|
Sign up to set email alerts
|

The co‐occurring use and misuse of cannabis and tobacco: a review

Abstract: Aims Cannabis and tobacco use and misuse frequently co-occur. This review examines the epidemiological evidence supporting the lifetime co-occurrence of cannabis and tobacco use and outlines the mechanisms that link these drugs to each other. Mechanisms include (a) shared genetic factors; (b) shared environmental influences, including (c) route of administration (via smoking), (d) co-administration and (e) models of co-use. We also discuss respiratory harms associated with co-use of cannabis and tobacco, overl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
376
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 455 publications
(409 citation statements)
references
References 122 publications
26
376
2
5
Order By: Relevance
“…Finally, cannabis and tobacco are often consumed together in the same joint and there is accumulating evidence of a common underlying biological vulnerability to both substances (Agrawal et al, 2012). Even if this study aims statistically to assess the independent effect of each substance on both medication adherence and remission, further research is needed to definitively disentangle their independent contribution on patients' clinical outcome.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Finally, cannabis and tobacco are often consumed together in the same joint and there is accumulating evidence of a common underlying biological vulnerability to both substances (Agrawal et al, 2012). Even if this study aims statistically to assess the independent effect of each substance on both medication adherence and remission, further research is needed to definitively disentangle their independent contribution on patients' clinical outcome.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Moreover, a laboratory study of non-treatment-seeking marijuana users revealed that co-smokers of cigarettes were more likely to relapse after a phase of cannabis abstinence compared with non-cigarette smokers [17]. Smoking cigarettes is assumed to provide behavioural and physiological cues for cannabis smoking and vice versa, which may explain the increased probability of relapsing among co-smokers [7,15]. In line with this hypothesis, a study analysed adolescents in substance-abuse treatment and found that never-smokers and those non-smokers who quit using tobacco during their marijuana treatment had a lower risk of marijuana relapse than those who continued or initiated tobacco smoking during treatment [16].…”
Section: Introductionmentioning
confidence: 99%
“…While cannabis dependence is usually treated in the psychiatric care system, interventions for tobacco users are part of the general public health system [18,19]. Recently, several reviews and a demand analysis identified a need for interventions tailored to co-smokers of tobacco and cannabis [7,[20][21][22]. To date, one small pilot study evaluated individual cognitive behavioural therapy combined with nicotine replacement therapy (NRT) for co-occurring cannabis and nicotine dependence [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, prototypical subgroups include: high chronic, decreasers, increasers, experimental users, abstainers, 'fling', rare. Conjoint/comorbid cannabis, alcohol, and tobacco use trajectories are also appearing [14,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%